2008
DOI: 10.1136/jmg.2008.059451
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic loss of function of the promyelocytic leukaemia zinc finger (PLZF) gene causes severe skeletal defects and genital hypoplasia

Abstract: The PLZF gene is one of five partners fused to the retinoic acid receptor alpha in acute promyelocytic leukaemia. We describe the first patient, to our knowledge, with a germline mutation of PLZF. Our findings as well as observations in Plzf-deficient mice indicate that PLZF is a key regulator of skeletal and male germline development. Furthermore, this case highlights the importance of searching for a recessive mutation on the non-deleted chromosome in patients with a microdeletion and atypical clinical findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 28 publications
3
50
0
Order By: Relevance
“…Color images available online at www.liebertpub.com/scd interstitial deletion in the 11q23 chromosomal region, which includes the ZBTB16 gene. This patient also revealed a recessive missense mutation (c. 1849ARG) within the remaining ZBTB16 allele [45,46]. This study indicated that ZBTB16 may play a critical role in the development of the skeleton and bone aging.…”
Section: Discussionmentioning
confidence: 83%
“…Color images available online at www.liebertpub.com/scd interstitial deletion in the 11q23 chromosomal region, which includes the ZBTB16 gene. This patient also revealed a recessive missense mutation (c. 1849ARG) within the remaining ZBTB16 allele [45,46]. This study indicated that ZBTB16 may play a critical role in the development of the skeleton and bone aging.…”
Section: Discussionmentioning
confidence: 83%
“…Adh1/Ptgis and their translated proteins influence tyrosine metabolism. Ttr/Zbtb16 and their translated proteins are involved in nerve regeneration (Fleming, Saraiva, & Sousa, 2007) and mental retardation (Fischer et al, 2008) (Tables 2 and 3). These neural events may be influenced by the CUMS.…”
Section: Discussionmentioning
confidence: 99%
“…3), orchestrated by BTB-mediated recruitment of chromatin remodeling factors to ZF-defined recognition sites, and there is increasing evidence that individual BTB-ZF proteins can influence multiple interactions with distinct proteins, as they can be separated by a point mutation in the BTB domain. 111 Genital hypoplasia is also a feature of human PLZF deficiency, 106 suggesting the conservation of both functions in man. Similar to PLZF, loss of PATZ1 causes male infertility due to a loss of spermatogonial stem cells;…”
Section: Discussionmentioning
confidence: 99%